Effect of acute static stretching on force, balance, reaction time, and movement tiime - Behm, D. G.; Bambury, A.; Cahill, F.; Power, K. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of the study was to investigate the effect of an acute bout of lower limb static stretching on balance, proprioception, reaction, and movement time. METHODS: Sixteen subjects were tested before and after both a static stretching of the quadriceps, hamstrings, and plantar flexors or a similar duration control condition. The stretching protocol involved a 5-min cycle warm-up followed by three stretches to the point of discomfort of 45 s each with 15-s rest periods for each muscle group. Measurements included maximal voluntary isometric contraction (MVC) force of the leg extensors, static balance using a computerized wobble board, reaction and movement time of the dominant lower limb, and the ability to match 30% and 50% MVC forces with and without visual feedback. RESULTS: There were no significant differences in the decrease in MVC between the stretch and control conditions or in the ability to match submaximal forces. However, there was a significant (P < 0.009) decrease in balance scores with the stretch (decreasing 9.2%) compared with the control (increasing 17.3%) condition. Similarly, decreases in reaction (5.8%) and movement (5.7%) time with the control condition differed significantly (P < 0.01) from the stretch-induced increases of 4.0% and 1.9%, respectively. CONCLUSION: In conclusion, it appears that an acute bout of stretching impaired the warm-up effect achieved under control conditions with balance and reaction/movement time.